Seasonal Distributions of Heavy Metals in Vellar River, Vellar Estuary and Portonovo Coastal Waters, South East Coast of India - C, Prabhahar. (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACTIn this present research work, the heavy metal contamination in Vellar River, Vellar estuary and Portonovo coastal waters, South East Coast of India was evaluated. In this study, heavy metals such as Zinc, Copper, Lead, Cadmium and iron were analyzed in the water samples. The sample analysis was done by microwave assisted digestion and Atomic Absorption Spectrophotometer.